2013
DOI: 10.1590/s0004-28032013000200040
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Malabsorption in Children With Functional Digestive Disorders

Abstract: -Context -Fructose is a monosaccharide frequently present in natural and artificial juice fruits. When the concentration of fructose in certain food is present in excess of glucose concentration some individuals may develop fructose malabsorption. Objectives -To report the frequency of fructose malabsorption utilizing the hydrogen breath test in children with gastrointestinal and/ or nutritional disorders. Methods -Between July 2011 and July 2012, 43 patients with gastrointestinal and/or nutritional disorders,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…However, a negative result does not exclude a satisfactory response to fructose restriction, therefore, hydrogen breath testing is not an appropriate diagnostic medium to predict diet response (Lozinsky et al, 2013). This test is based on the fact that normal intestinal flora metabolizes these sugars into short chain fatty acids and hydrogen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a negative result does not exclude a satisfactory response to fructose restriction, therefore, hydrogen breath testing is not an appropriate diagnostic medium to predict diet response (Lozinsky et al, 2013). This test is based on the fact that normal intestinal flora metabolizes these sugars into short chain fatty acids and hydrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Some eating disorders present similar treatment to HFI, such as fructose malabsorption, which is a functional problem of the small intestine, triggered by a decrease in fructose absorption capacity, and may be caused by the excessive intake of fructose and consequent disorders in the intestinal microbiota or even to be secondary to an underlying intestinal disease such as celiac disease (Canani et al, 2016). Its symptoms are like those of the HFI, but with a lower intensity, being more related to emetic episodes, abdominal pain, bloating, abdominal distension and diarrhea after ingestion of foods rich in fructose, sucrose or sorbitol (Lozinsky et al, 2013). The test of expiratory hydrogen can be used to aid in the diagnosis, but the therapeutic test with the suspension of foods rich in fructose presents a greater diagnostic and therapeutic accuracy (Yüce et al, 2016;Canani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To Horst et al 11 , somatic intestinal symptoms and depression in children with FAP were relevant for the maintenance of the abdominal pain from childhood into the adult life. The influence of physiological symptoms and digestive processes was presented by Lozinsky et al 12 , who found a poor fructose absorption in 30.2% of the subjects diagnosed with irritable bowel syndrome and FAP. Children in the FAP group presented greater response of the parasympathetic system 13 , which means more difficulty in reaching the homeostasis state than in children in the painless group, as well as the deregulation of the autonomic system against the FAP mechanism.…”
Section: Category 1 Factors Associated With Functional Abdominal Painmentioning
confidence: 94%